Residual effect of NPK fertilization (methods and time) on upland cotton submitted to two pruning times - Nóbrega, Laudemiro Baldoino da; Beltrão, Napoleão Esberard de Macêdo; Azevedo, Demóstenes Marcos Pedrosa de (Pesquisa Agropecuaria Brasileira, 2014)
A field trial was conducted in 1979 and 1980, at São Bento, PB, Brazil, a physiographic zone of Sertão, on an uncultivated sandy medium-natural fertility soil, to study the effects of fertilization with macronutrients (methods and dates of nitrogen and potassium application) at the first year, and their residual effects at the second year, when the cotton (Gossypium hirsutum L.) crop was submitted to two pruning dates. Allen 333-57, a commercial cultivar, was planted at the spacing of 1 m apart, with five plants per meter of row, amounting a population of 50.000 plants per hectare. At the first year no significative effects of fertilization was detected. It was found, however, that when phosphoric and potassic fertilizers were applied at plating to a side of the row and nitrogen 65 days after emergence, the cotton yield was increased by 23%. No important difference was observed in the second year between method and date of fertilizer application especially for pruning made in the dry season before the first rain. On the other hand, pruning in the dry season made it possible to obtain a yield of 1,951 kg/ha in contrast to 1,324 kg/ha by pruning at the beginning of the rainy season. Fertilization promoted a 73% yield increase (2,003 in contrast to 1,158 kg/ha) when the pruning was made at the dry season, which caused a decrease to 17% when the pruning was made after the first rain.